(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Perception is not a simple sum of sensations. In the process of perception, in addition to sensetations, previous experience, awareness of the perceived, as well as memory processes are involved. Also, in many cases, perception is called the human perceptual system.